Using drawings to bridge the transition from student to future teacher of mathematics - Ji-Eun Lee; Mary Zeppelin (International Electronic Journal of Elementary Education, 2014)
This study examines a group of prospective teachers’ reflections upon the way they were taught (Set 1) and the way they want to teach (Set 2) through drawings which respectively describe their past learning experiences as students and their future plans as teachers. The purpose of this study is to identify: (a) the emerging themes that appear in each set of drawing data, (b) the possible factors that influence prospective teachers’ drawings, and (c) the implications for mathematics teacher educators. Overall, prospective teachers showed predominantly negative or mixed feelings about their past experiences as mathematics students. In response to their own past negative experiences and struggles, the prospective teachers tended to highlight emotionally supportive classroom environment and versatile instructional teaching strategies in their future plans. This study suggests that this activity of reflecting past experience and planning future teaching assimilates prospective teachers’ identities as math students and math teachers and provides a window into the thinking of others.